2018
DOI: 10.1007/s10802-017-0396-0
|View full text |Cite
|
Sign up to set email alerts
|

Examining the Prospective Relationship between Pre-Disaster Respiratory Sinus Arrhythmia and Post-Disaster Posttraumatic Stress Disorder Symptoms in Children

Abstract: Previous studies have examined the concurrent relationship between posttraumatic stress disorder (PTSD) and a range of psychophysiological variables, including respiratory sinus arrhythmia (RSA). However, there is a lack of research examining the prospective development of trauma symptomatology, and the directionality of the association between RSA level and PTSD has yet to be determined. The current study is the first prospective study to examine whether RSA level and RSA reactivity are risk factors for PTSD … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 38 publications
(61 reference statements)
1
8
0
Order By: Relevance
“…Predictions are controlled for age, time between traumatic event and T2 as well as pre-treatment PTSD symptoms. Mikolajewski & Scheeringa, 2018;Minassian et al, 2015;Morris et al, 2016;Pyne et al, 2016;Shaikh Al Arab et al, 2012) We assessed HR(V) parameters during rest within the first 12 days posttrauma and did not observe any prognostic effects. The comparison with previous findings suggests that resting HR(V) measured before or acutely after trauma has prognostic value, whereas this value diminishes over time, supporting the recommendation to apply a stage-dependent approach to investigate biological mechanisms associated with PTSD (McFarlane, Lawrence-Wood, van Hooff, Malhi, & Yehuda, 2017).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Predictions are controlled for age, time between traumatic event and T2 as well as pre-treatment PTSD symptoms. Mikolajewski & Scheeringa, 2018;Minassian et al, 2015;Morris et al, 2016;Pyne et al, 2016;Shaikh Al Arab et al, 2012) We assessed HR(V) parameters during rest within the first 12 days posttrauma and did not observe any prognostic effects. The comparison with previous findings suggests that resting HR(V) measured before or acutely after trauma has prognostic value, whereas this value diminishes over time, supporting the recommendation to apply a stage-dependent approach to investigate biological mechanisms associated with PTSD (McFarlane, Lawrence-Wood, van Hooff, Malhi, & Yehuda, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…To date, three prospective studies investigated pretrauma HRV. These reported that pretrauma lower resting HRV was associated with higher posttrauma PTSD symptoms in male military personnel (Minassian et al, 2015 ) and a mixed-sex sample of children (Mikolajewski & Scheeringa, 2018 ). The third study, again in a predominantly male, military personnel sample, found this association was specific to the context of high pretrauma symptoms (Pyne et al, 2016 ).…”
Section: Introductionmentioning
confidence: 99%
“…Following a disaster, perhaps youth with a specific genotype or neural dysfunction may be more likely to manifest trauma response through the development of co-occurring PTS and CPs. For example, research has shown that genetic variations interact with maltreatment to influence youth aggression (Bryushkova et al, 2016), and youth Respiratory Sinus Arrhythmia before a natural disaster predicts post-disaster PTSD symptoms (Mikolajewski & Scheeringa, 2018). Similar physiological and neural pathways are implicated in youth PTS and CPs (e.g., Blair, Veroude, & Buitelaar, 2018; Morey, Haswell, Hooper, & De Bellis, 2016), perhaps accounting in part for the overrepresentation of CP among youth with the most severe PTS.…”
Section: Discussionmentioning
confidence: 99%
“…Of the eight studies that measured indices of the autonomic nervous system (ANS), all eight supported the DST in relation to one or more variables Guthrie & Bryant, 2005, 2006Mikolajewski & Scheeringa, 2016;Minassian et al, 2015;Orr et al, 2012;Pole et al, 2009;Pyne et al, 2016). Two of the studies also repeated the measurement of an ANS variable after the index trauma and were capable of testing the NST, and both were negative for the NST (Guthrie & Bryant, 2005;Mikolajewski & Scheeringa, 2016).…”
Section: Autonomic Stress Response Systemsmentioning
confidence: 99%
“…Many of the subjects in these studies experienced traumas prior to their index traumas in the studies. However, two studies included samples with no prior trauma exposure and both found support for the DST Mikolajewski & Scheeringa, 2016). The majority of participants in the studies were self-selected individuals who entered military and first-responder careers.…”
Section: Limitationsmentioning
confidence: 99%